The Significance Of Intent On Zakatable Real Estate: A Juristic Analysis - Saheed Abdullahi Busari; Miszairi Sitris; Luqman Zakariyah (USIM Press, 2024)
Vol. 9 No. 2 (2021): MJSL - Volume 9, No. 2, 2021